Right-wing populism in Europe : politics and discourse - Wodak, Ruth 1950- Hrsg; Khosravinik, Majid; Mral, Brigitte 1953- (Bloomsbury, 2013)
"Right-wing populist movements and related political parties are gaining ground in many EU member states. This unique, interdisciplinary book provides an overall picture of the dynamics and development of these parties across Europe and beyond. Combining theory with in-depth case studies, it offers a comparative analysis of the policies and rhetoric of existing and emerging parties including the British BNP, the Hungarian Jobbik and the Danish Folkeparti. The case studies qualitatively and quantitatively analyse right-wing populist groups in the following countries: Austria, Belgium, Britain, Denmark, Estonia, France, Germany, Greece, Hungary, Italy, Latvia, Netherlands, Norway, Sweden, Switzerland and Ukraine, with one essay exclusively focused on the US. This timely and socially relevant collection will be essential reading for scholars, students and practitioners wanting to understand the recent rise of populist right-wing parties at local, countrywide and regional levels in Europe and beyond."--Page 4 of cover